The Impact of Fear and Anti-Predator Behavior on the Dynamics of Stage-Structure Prey–Predator Model With a Harvesting - Majeed, Azhar Abbas (Iraqi Journal of Science, 2024)
In this paper, an ecological model with stage-structure in prey population, fear, anti-predator and  harvesting are suggested. Lotka-Volterra  and Holling type II functional responses have been  assumed to describe the feeding processes . The local and global stability of steady points of this model  are  established. Finally, the global dynamics are studied numerically to investigate the influence of the parameters on the solutions of the system, especially the effect of fear and anti-predation.